DETERMINASI YANG BERKONTRIBUSI TERHADAP KINERJA KARYAWAN - Elsa Meirina; Mike Kusuma Dewi (Universitas La Tansa Mashiro, 2025)
This study aims to analyze the influence of leadership and organizational commitment on employee performance at PT Pos Indonesia (Persero) Padang Branch. The study used a quantitative approach, with a sample of 40 employees selected through simple random sampling. Data were obtained through questionnaires and analyzed using multiple linear regression. The results showed that leadership had no significant effect on employee performance, while organizational commitment had a positive and significant effect. Simultaneously, both variables significantly influenced performance. This finding confirms that improved performance is more influenced by strong organizational commitment than leadership style.